COMPARATIVE SUITABILITY BETWEEN TOXICITY ASSAY BY USING IN SILICO AND IN VIVO OF SEVERAL COMPOUNDS AS ANTIVIRAL âA REVIEW - Hadiah Akbar, Nabila
Toxicology is the study of adverse effects or toxic effects of chemicals on living organisms. Initially, the toxicity test was carried out in vivo, but now starting to develop into the in silico toxicity test. However, the in silico toxicity test is still not widely used. Therefore, the purpose of this literature review is to explain the in vivo toxicity test, the in silico toxicity test and also to compare the suitability of the in silico toxicity test results with the in vivo toxicity test for some antiviral drugs. The inclusion criteria used were the in silico toxicity test, in vivo toxicity test, and antivirals for which in silico toxicity test data were available. While the exclusion criteria used were in vitro and antiviral toxicity tests for which no in silico toxicity test data were available. This literature review uses 146 sources, divided into 100 journals, 33 reviews, and 13 books. The 146 sources were also divided into 76 sources used to make literature studies related to in vivo toxicity tests, 17 sources used to make literature studies related to in silico toxicity tests, 49 sources used to make literature studies related to toxicity tests on 14 antiviral compounds and 4 sources were used to create the introduction. Sources were obtained through the PubMed search engine, Science direct, and google scholar with data search times from September 2020 to December 2020. The results of the literature review conducted are In vivo toxicity tests consists of acute oral toxicity, subchronic oral toxicity test, chronic oral toxicity test, teratogenicity test, skin sensitization test, eye irritation test, acute dermal irritation test, vaginal mucosal irritation test, dermal acute toxicity test and dermal subchronic toxicity test. In vivo toxicity testing is also now starting to develop using zebrafish (Danio rerio). In silico toxicity tests are divided into 3 types, Structure - Activity relationship (SAR), Quantitative Structure - Activity Relationship (QSAR), and Read-Across (expert ruled-based system / expert rule-based system). Comparison of in silico and in vivo toxicity test on eltrombopag produces the same result, it is stated as hepatotoxic ; simeprevir produces the same result, it is stated as hepatotoxic ; andrographolide produce almost the same result, which is in silico is expressed as slightly toxic while in vivo result are obtained as Non-toxic compound ; caffeic acid showed the same result, it is stated as not teratogenic ; quercetin produced the same result, that it has mutagenic properties ; and isoquercitrin also produced the same result, that it was not carcinogenic. Meanwhile, favipiravir produced different result, that in silico it was not stated to be toxic, while in vivo it was found to have teratogenic and embryotoxic properties. In the modification of viramidine, xanthosine, inosine; 2 derivatives of zanamivir; and the degradation results of sofosbuvir and oseltamivir phosphate only showed the in silico toxicity test results, while the in vivo toxicity test did not exist. In conclusion, review analysis showed a suitability between the in silico and in vivo toxicity test on antiviral compounds for mutagen, carcinogens, hepatotoxic and teratogenic end points as much as 85.7%. Thus, the in silico toxicity test can be used as a preliminary toxicity test to select compounds that need to be carried out in vivo further toxicity tests in the development of new drugs.